Redução de cromo hexavalente utilizando-se filmes de polímeros condutores como materiais eletródicos - Ruotolo, Luis Augusto Martins (Universidade Federal de São Carlos, 2003)
In this work we studied a three-dimensional electrode (reticulated vitreous carbon, CVR), modified with conducting polymer films, for the electrochemical reduction of Cr(VI). First of all, the conducting polymers polyaniline (PANI) and polypyrrole (PPY) were tested under open circuit conditions. Both polymers showed to be unstable under this condition. Polypyrrole was partially degraded while polyaniline was totally degraded, suggesting that the process under open circuit condition is not possible . We tested a new methodology called cathodic protection of the film, which had very good results for polyaniline, increasing the reaction rate and preserving the stability of the polymer film. Nevertheless, the reaction of Cr(VI) reduction using polypyrrole under cathodic protection condition was not successful because of the degradation of the polymer. Before these results we decided to use only polyaniline in further studies. The process was evaluated in terms of its current efficiency, space-time yield and energy consumption as a function of flow velocity, electric current (or current density), Cr(VI) concentration and thickness and porosity of the CVR electrode. In order to know the electrochemical activity inside the porous electrode, overpotential profiles were also measured. The results showed that thin thickness CVR/PANI electrodes optimize the electrochemical cell. An increase in flow velocity increases the mass transfer coefficient and the reaction rate up to a point after which an increase in flow velocity become insignificant because of hydrodynamic limitations. Increasing the electric current there is an increase in the space-time yield too, but after a value of current, its increase is not advantageous because the reaction of hydrogen takes place and consequently, the current efficiency of the process decreases. The effect of the Cr(VI) depletion was evalueted in curves of normalized concentration of Cr(VI) versus time, where is possible to see three different regions controling the process. From the initial concentration up to the so called transition concentration, C*, the process is controlled by activation and in this region the reaction rate is constant and the best current efficiencies, space-time yields and energy consumptions are found. At the end of the process, when the concentration is very low, the process is mass transfer controlled. In the intermediary region, just after C*, there is a region under mixed control. Based on the values of C* as a function of the current and flow velocity, we proposed a process optimization. Controlling the applied current as a function of Cr(VI) in the electrolyte we got high values of current efficiency and spacetime yeilds and low values of energy consumption. We finish applying the optimized electrochemical process to treat an effluent containing Cr(VI) from a valve factory. The analysis of the process was done as a function of the number of electrodes employed and the operational time used to treat the waste. From the cost analysis we conclude that a reactor with few electrodes and an operational time of twenty hours is quite convenient in order to decrease the investment cost and reduce the investment return time.
Keywords: Efluentes líquidos; Polipirrol; Polianilina; Carbono vítreo reticulado; Tratamento de efluentes; ENGENHARIAS::ENGENHARIA QUIMICA